Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's University Press, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Section: xxi, 157 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques

Femmes, genre, migration et mobilités - Catarino, Christine; Morokvasic, Mirjana (Revue européenne des migrations internationales, 2005)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; antiracisme; approches et analyses; cours; discipline; europe; france; féminisme décolonial; inégalités; migration; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques

Mondialisation et migrations féminines internationales, L’esclavage au cœur de la modernité - Ouali, Nouria (Les cahiers du CEDREF, 2003)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; afrique; afrique du nord; approches et analyses; belgique; cours; discipline; droit des femmes*; europe; inégalités; justice sociale; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

La scission politique du féminisme international sur la question du “ trafic des femmes ” vers la “ migration ” d’un certain féminisme radical ? - Toupin, Louise (Recherches féministes, 2003)
Cet article donne un aperçu de l’argumentation qui met en lumière et différencie les principales coalitions internationales féministes luttant contre ce qui est couramment appelé le « trafic des femmes ». L’argumentation mise en évidence ne touche que la définition du phénomène et le différend qui sépare les coalitions sur le sujet, ainsi que leurs stratégies respectives pour l’éradiquer. L’auteure souligne en conclusion certains tangentes du féminisme radical qui, à son avis, se voient désormais remises en cause à l’occasion du débat sur les migrations des femmes. Ce débat entraînera-t-il, à son tour, se demande-t-elle, la migration d’un certain féminisme radical ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; histoire du féminisme; histoire et politique; intersectionnalité; miitance; patriarcat; premier cycle; prostitution; périodes historiques; ressource en ligne; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; traite des femmes; travail; travail du sexe; violences